Prenatal diagnosis of mosaicism for double aneuploidy of 47,XXY and trisomy 7 (48,XXY,+7) at amniocentesis in a pregnancy with a favorable outcome - Chih-Ping Chen; Hsiu-Ting Tsai; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Fang-Tzu Wu; Yun-Yi Chen; Dai-Dyi Town; Wen-Lin Chen; Meng-Shan Lee; Wayseen Wang (Elsevier, 2021)
Objective: We present prenatal diagnosis of mosaicism for double aneuploidy of 47, XXY and trisomy 7 (48,XXY,+7) at amniocentesis in a pregnancy with a favorable outcome. Case report: A 33-year-old woman underwent amniocentesis at 17 weeks of gestation because of an increased risk for Down syndrome in maternal serum screening. Amniocentesis revealed a karyotype of 48,XXY,+7[8]/46,XY[16]. Simultaneous array comparative genomic hybridization (aCGH) analysis on uncultured amniocytes revealed the result of arr [GRCh37] (7) × 3 [0.54], (X) × 2 [0.52], (Y) × 1, compatible with trisomy 7 mosaicism and Klinefelter syndrome mosaicism. The parental karyotypes and prenatal ultrasound findings were normal. Repeat amniocentesis performed at 23 weeks of gestation revealed a karyotype of 48,XXY,+7[13]/46,XY[7]. Simultaneous molecular cytogenetic analyses on uncultured amniocytes revealed 30% mosaicism for 48,XXY,+7 by aCGH and 37% (37/100 cells) mosaicism for trisomy 7 and disomy X by interphase fluorescence in situ hybridization (FISH) analysis. Polymorphic DNA marker analysis excluded uniparental disomy (UPD) 7 and indicated a maternal origin of the chromosome aberration. The pregnancy was continued to 39 weeks of gestation, and a 3070-g healthy male baby was delivered. The cord blood had a karyotype of 46,XY, the umbilical cord had a karyotype of 48,XXY,+7[3]/46,XY[37], and the placenta had a karyotype of 48,XXY,+7. At age one month, the neonate was phenotypically normal, and interphase FISH analysis revealed 4.8% (5/105 cells) mosaicism on buccal mucosal cells and 8.9% (8/90 cells) mosaicism on urinary cells for trisomy 7 and disomy X, compared with 2% in normal control. Interphase FISH analysis on buccal mucosal cells at age two months revealed normal findings in 100/100 cells. Conclusion: Mosaic 48,XXY,+7 at amniocentesis without UPD 7 can be associated with a favorable fetal outcome. Cytogenetic discrepancy between cultured amniocytes and uncultured amniocytes may occur in mosaic 48,XXY,+7 at amniocentesis.